Motives For Purchase of Skin Care Product Users (Phenomenology Study on Women in DKI Jakarta) - Luthfi Aulia Faza; Prima M Agustini; Siti Maesaroh; Andri Cahyo Purnomo; Efa Ayu Nabila (ADI Publisher, 2022)
This study aims to analyze the purchasing motives of users of skin care products, and is a phenomenological study of women in DKI Jakarta. To find out this motive, researchers used a qualitative approach, which aims to explore the true meaning of women's motives for buying skin care products. The data used for this study are primary data and secondary data. The results of a research analysis using in depth interviews with women in DKI Jakarta who bought skin care products, that they made skin care purchases with Hedonic Shopping motives. Motivations for women in DKI Jakarta using skin care products were motives, namely Adventure shopping and Social Shopping, while utilitarian Shopping motivation is motivation needs.